2020
DOI: 10.1002/cssc.201903286
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Conversion of Lignin into Naphthenes Catalyzed by a Heterogeneous Rhenium Oxide‐Modified Iridium Compound

Abstract: The direct transformation of lignin into fuels and chemicals remains a huge challenge because of the recalcitrant and complicated structure of lignin. In this study, rhenium oxide‐modified iridium supported on SiO2 (Ir‐ReOx/SiO2) is employed for the one‐pot conversion of various lignin model compounds and lignin feedstocks into naphthenes. Up to 100 % yield of cyclohexane from model compounds and 44.3 % yield of naphthenes from lignin feedstocks are achieved. 2 D HSQC NMR spectroscopy before and after the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 60 publications
1
32
0
Order By: Relevance
“…It is also reported that ReO x NPs contain ammonium ion, which is probably a Brønsted acid site in the catalyst [22]. In addition to dehydration, the acid sites on [32]. The control test without catalyst under the same conditions (250 • C, 1 h) yielded ester compounds (Figure 1a).…”
Section: Conversion Of Succinic Acid (Sa)mentioning
confidence: 75%
“…It is also reported that ReO x NPs contain ammonium ion, which is probably a Brønsted acid site in the catalyst [22]. In addition to dehydration, the acid sites on [32]. The control test without catalyst under the same conditions (250 • C, 1 h) yielded ester compounds (Figure 1a).…”
Section: Conversion Of Succinic Acid (Sa)mentioning
confidence: 75%
“…A transformation of lignin into smaller units by a hydrogen source can lead either to complete reduction (cycloalkanes) or aromatic compounds (phenols, guaiacol, and syringols), depending on reaction conditions, such as H 2 pressure [50,57] . Occasionally, complete hydrogenation of lignin by H 2 is avoided for aromatic monomers production.…”
Section: Hydrogenation Of Platform Moleculesmentioning
confidence: 99%
“…IrÀ ReO x /SiO 2 with Lewis acid sites (Figure 8b, v˜= 1450 and 1490 cm À 1 ) and Brønsted acid sites (v˜= 1540 and 1490 cm À 1 ) showed an extraordinarily high catalytic activity in the one-pot hydrogenolysis of lignin feedstocks and lignin model compounds into naphthene. [117] The excellent activity of IrÀ ReO x /SiO 2 has mostly resulted in the synergistic effect between the hydrogenating sites on Ir 0 and acidic sites on ReO x /SiO 2 . Compared with noble metal Ir, mesoporous silica supported Ni-based catalysts are more common and economical in hydrogenolysis of lignin.…”
Section: Mesoporous Silica-based Catalystsmentioning
confidence: 99%
“…b) FTIR spectra of adsorbed pyridine on Ir/SiO 2 , ReO x /SiO 2 , and IrÀ ReO x /SiO 2 . [117] Reused with permission. Copyright 2020, Wiley-VCH.…”
Section: Niobium Phosphate Supported Catalystsmentioning
confidence: 99%